2015
DOI: 10.3174/ajnr.a4287
|View full text |Cite
|
Sign up to set email alerts
|

Direct Cranial Nerve Involvement by Gliomas: Case Series and Review of the Literature

Abstract: Malignant gliomas are characterized by infiltrative growth of tumor cells, including along white matter tracts. This may result in clinical cranial neuropathy due to direct involvement of a cranial nerve rather than by leptomeningeal spread along cranial nerves. Gliomas directly involving cranial nerves III-XII are rare with only eleven cases reported in the literature prior to 2014, including eight with imaging. We present eight additional cases demonstrating direct infiltration of a cranial nerve by glioma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 25 publications
1
46
1
Order By: Relevance
“…An autopsy was performed on this patient following palliative radiation and chemotherapy, and histone H3-K27M immunohistochemistry was helpful in assessing the widespread infiltration of the tumor cells throughout the brain and spinal cord. Tumor cells were seen infiltrating from the brainstem into multiple cranial nerves (Figures 3H and I), a finding that has only been rarely observed in malignant gliomas (22). …”
Section: Resultsmentioning
confidence: 80%
“…An autopsy was performed on this patient following palliative radiation and chemotherapy, and histone H3-K27M immunohistochemistry was helpful in assessing the widespread infiltration of the tumor cells throughout the brain and spinal cord. Tumor cells were seen infiltrating from the brainstem into multiple cranial nerves (Figures 3H and I), a finding that has only been rarely observed in malignant gliomas (22). …”
Section: Resultsmentioning
confidence: 80%
“…Cranial nerve glioblastomas are presumably originated from CNS tissue locating at the root entry zone of the cranial nerve or from heterotopic neuroglia cells in the leptomeninges. Similarly, Mabray et al [17] recently reported eight cases of glioblastoma originated from the cranial nerve. These glioblastomas were located at the CPA and involved the unilateral brainstem.…”
Section: Discussionmentioning
confidence: 91%
“…Matsuda et al [18] reported a case of glioblastoma originated from the cerebellum and reviewed another three similar cases. In the reports by both Mabray et al [17] and Matsuda et al [18], the relatively clear boundary between the brainstem and tumor were demonstrated during the operation. In our case, neither preoperative MRI nor surgery alone supported an origin at the cranial nerve cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, although several factors have been reported to exhibit correlation with the initiation and development of cranial nerve involvement, the mechanism of interactions between cranial nerve involvement and affecting factors remain to be fully elucidated (24). Several potentially neuroprotective agents function to upregulate gene transcription at the onset of brain ischemia, which may be an effective approach for limiting brain tissue damage (25). Studies on the mechanisms of cranial nerve involvement have shown that the serotonin systematic signaling pathway shows high correlation with the initiation, development, treatment and prognosis of cranial nerve involvement (26,27).…”
Section: Discussionmentioning
confidence: 99%